The Diagnostic and Therapeutic Application of Laser Exclusively in the Periodontal Field - Rashmita Nayak1, Abhijeeta Mahapatra2, Rinkee Mohanty3, Abhaya C. Das4, Gatha Mohanty5, Utkalika Das (Indian Journal of Forensic Medicine & Toxicology, 2020)
When laser energy is used as a therapy modality for the prevention, treatment, and management of differenttypes of periodontal disease, it emerged into a very exciting therapeutic tool bringing a huge success withit. Various types of lasers are available today in the modern technology world. Along with the types oflasers, also available the various options to choose the right wavelength according to the treatment modality.Not only is the laser used for root surface procedures, but also the soft tissue manipulation in the field ofPeriodontology. This makes periodontal treatment by dental laser a grand success as reported in a myriadof literature. The only mandatory condition applied to be applied is the sound knowledge of the clinicianin choosing the right type of laser with the required wavelength for a particular periodontal procedure. Noother field of dentistry still has seen so many marvelous transformations in the healing and success in themanagement of the soft tissue after a periodontal procedure. There is a huge application of the usage of Laserin the periodontal world exclusively, which is the goal of this review paper.